Market Research Applicability Among Nigerian Estate Surveyors and Valuers in Project Appraisal - Gambo, Y. L.; Otegbulu, A. C.; Omirin, M. M.; Osagie, J. U. (Mediterranean Journal of Social Sciences, 2012)
An investigation into market research applicability among Estate surveyors and Valuers examined the competence with whichprofessionals carry out market research while on project appraisal. Structured questionnaires were analyzed using appropriate inferentialand descriptive statistical tools. The study revealed Estate Surveyors and Valuers carry out market research in feasibility studiesshabbily and without the required competence. The study also revealed that Estate Surveyors and Valuers spend little or no time incarrying out market research compared to the onerous task required in market research. This by implication obviously affects even themost viable investment decision. It recommended the need for the Nigerian Institution of Estate Surveyors and Valuers to providestandardized methodological framework within the context of project appraisal for market research and to actively play a supervisory roleto ensure Estate Surveyors and Valuers adhere to minimum practice standards.